Perancangan dan Pembuatan Sistem Informasi E-Learning Menggunakan Web Framework CodeIgniter Studi Kasus: SMA Ksatrya Jakarta - Qoyyimah, Lulu Dinnul; Whendasmoro, Raditya Galih; Kurnia, Mega Tri (FIKOM - Bung Karno University, 2023)
The influence of information and communication technology on the world of education is rapidly evolving, shifting the learning paradigm from face-to-face teaching to media-based learning. SMA Perguruan Ksatrya Jakarta, under the Yayasan Perguruan Ksatrya, focuses on innovation in the field of education. However, the current learning system remains manual, relying on face-to-face interactions between teachers and students, which are limited in discussions and interactions. This condition leads to a lack of achieving learning targets. This research aims to design an e-learning information system using the CodeIgniter framework. The selection of CodeIgniter is expected to facilitate e-learning, enhance efficiency, and improve the accuracy of learning management. System development involves PHP and MySQL, designed based on UML principles. The research output yields an e-learning information system aimed at enhancing the understanding of the teaching and learning process at SMA Ksatrya. This system is anticipated to support more dynamic interaction between teachers and students while expediting the learning process following the SDLC method. SMA Ksatrya Jakarta has the potential to enhance the quality of learning, facilitate better interaction, and expedite the learning process in line with the strategically set objectives.